Investigating the Important Factors of Use and Replacement of Thirsty Concrete Materials in Urban Development. Issue 1 (29th September 2020) - Atakara, Cemil; Ramezani, Hoda
Sustainable has recently become the favorite subject of many disciplines due to sustainable development. Nowadays, due to the environmental problems of the construction industry, the development of materials, products, and methods of construction, sustainable architecture leads to higher efficiency, better economic cost, and environmental sustainability. It can be supposed sustainable development means preserving nature also fulfil the human needs through modern technologies. One of the goals of sustainable development is to construct with less energy consumption and a long life that in this part, materials play an important role in content production. the most important role that materials and structures can play is to help people survive natural disasters and respect nature by using it properly. For example, in some areas, floods and rainfalls cause many Life and financial damages, and on the other hand, some countries by consecutive droughts try to manage drinking water. Meanwhile, it is claimed that with the help of smart materials, these wastes can be prevented and using optimization of environment and renewable energy. Creating this harmony between man and nature has given rise to a new challenge in many fields. For this reason, this paper seeks to address the challenge of using thirsty concrete, a type of smart material and sustainable architectural innovation, to coordinate between old, present and future structures. Therefore, by using a qualitative method, these materials will be studied and some samples would be used, followed by a quantitative method of analysis of the usage of these materials in Barış Park in Kyrenia which is the intersection of historical place and contemporary one.